Effect of Manganese Ions on Spectroscopic and Insulating Properties of Aluminophosphate Glasses. (29th June 2021) - Kassa, B.; Leta Tesfaye, J.; Bulcha, B.; Kiran, R.; Deepak, T.; Lal, Dayanand; Venkatesh, S.; Krishnaraj, R.
Abstract : The melt-quenching technique was used to produce 39CdO–10Al2 O3 -(51- x ) P2 O5 : x MnO glasses ( x  = 0, 0.1, 0.2, 0.3, and 0.4 wt.%). Various stability factors were calculated and presented from DTA analysis. The stability of the glass network appears to increase with the increase of MnO concentration, according to the findings. IR spectral analysis of these glasses exhibited several symmetrical and asymmetrical bands due to phosphate groups. The observed change in these band intensities with the rise in MnO concentrations, ranging from 0.1 wt.% to 0.4 wt.%, shows an increase in the stability of the glass network. Optical absorption analyses of these glasses revealed an absorption band that shifted from 500 to 488 nm as the concentration of manganese oxide (MnO) increased from 0.1 wt.% to 0.4 wt.%, indicating that Mn 2+ ions were gradually converted into Mn 3+ ions. EPR spectra of these glasses were characterized by two signals due to Mn 2+ and Mn 3+ ions. Observations on these signal intensity variations revealed an increase in stability of the glass network with the increase of MnO concentration from 0.1 wt.% to 0.4 wt.%. Parameters, which describe the insulating characteristics, for example, dielectric constant, ε, dielectric loss, tan δ, and AC conductivity σ ac, were determined in relation to frequency (10 3  Hz to 10 5  Hz) and temperature (20°C to 400°C) and presented in the dielectric analysis of these glasses.